CVD controlled growth of large-scale WS2 monolayers. Issue 51 (19th September 2019) - Xu, Zhuhua; Lv, Yanfei; Li, Jingzhou; Huang, Feng; Nie, Pengbo; Zhang, Siwei; Zhao, Shichao; Zhao, Shixi; Wei, Guodan
Abstract : Monolayer tungsten disulfide (WS2 ) with a direct band gap of ca. 2.0 eV and stable properties has been a hotspot in two-dimensional (2D) nanoelectronics and optoelectronics. Abstract : Monolayer tungsten disulfide (WS2 ) with a direct band gap of ca. 2.0 eV and stable properties has been a hotspot in two-dimensional (2D) nanoelectronics and optoelectronics. However, it remains challenging to successfully prepare monolayer WS2 . In this paper, we report the chemical vapor deposition (CVD) growth behavior of hexagonal WS2 monolayers by using WS2 powders and sodium triosulfate (Na2 S2 O3 ) as precursors. We observed the Na2 S2 O3 has a significant effect on the WS2 triangular and leaf-like shapes. In addition, based on proposed S-termination and W-termination theory, the growth mechanisms for different shapes of WS2 were discussed.